Interim recommendations for use of the inactivated COVID-19 vaccine BIBP developed by China National Biotec Group (CNBG), Sinopharm : interim guidance : 7 May 2021, updated 15 March 2022 (World Health Organization, 2022)
These WHO interim recommendations for use of the COVID-19 vaccine BIBP produced by Sinopharm were developed on the basis of advice issued by the Strategic Advisory Group of Experts on Immunization (SAGE) and the evidence summary included in the background document and annexes referenced below.
Keywords: epidemický výskyt choroby; veřejné zdravotnictví; Disease Outbreaks; preventivní medicína; vakcíny proti COVID-19; COVID-19 Vaccines; Betacoronavirus; COVID-19; infekční lékařství